Effects of Atractylodis Rhizoma Pharmacopuncture on an Acute Gastric Mucosal Lesion Induced by Compound 48/80 in Rats - Lee Yun-Kyu; Kim Jae-Soo; Lim Seong-Chul (Korean Pharmacopuncture Institute, 2012)
Objectives: This study was designed to investigate the protective effects of Atractylodis Rhizoma pharmacopuncture (ARP) against acute gastric mucosal lesions induced by compound 48/80 in rats. Methods: The ARP was injected in Joksamni (ST36) and Jungwan (CV12) 1 hr before treatment with compound 48/80. The animals were sacrificed under anesthesia 3 hrs after treatment with compound 48/80. The stomachs were removed, and the amounts of gastric adherent mucus, gastric mucosal hexosamine, thiobarbituric acid reactive substances (TBARS), xanthine oxidase (XO), and superoxide dismutase (SOD) were measured. Also, histological examination were performed. Results: Gastric adherent mucus, gastric mucosal hexosamine and histological defects of gastric mucosa declined significantly after ARP treatment. Changes in gastric mucosal TBARS were also reduced by ARP treatment, but this result was not statistically significant. ARP treatment did not change the XO and the SOD activities. Conclusions: ARP showed protective effects for acute gastric mucosal lesions induced by compound 48/80 in rats. These results suggest that ARP may have protective effects for gastritis.